Metabotropic glutamate receptor orthosteric ligands and their binding sites. (15th February 2022) - Acher, Francine C.; Cabayé, Alexandre; Eshak, Floriane; Goupil-Lamy, Anne; Pin, Jean-Philippe
Abstract: Metabotropic glutamate receptors (mGluRs) have been discovered almost four decades ago. Since then, their pharmacology has been largely developed as well as their structural organization. Indeed mGluRs are attractive therapeutic targets for numerous psychiatric and neurological disorders because of their modulating role of synaptic transmission. The more recent drug discovery programs have mostly concentrated on allosteric modulators. However, orthosteric agonists and antagonists have remained unavoidable pharmacological tools as, although not expected, many of them can reach the brain, or can be modified to reach the brain. This review focuses on the most common orthosteric ligands as well as on the few allosteric modulators interacting with the glutamate binding domain. The 3D-structures of these ligands at their binding sites are reported. For most of them, X-Ray structures or docked homology models are available. Because of the high conservation of the binding site, subtype selective agonists were not easy to find. Yet, some were discovered when extending their chemical structures in order to reach selective sites of the receptors. This article is part of the Neuropharmacology Special Issue on 'Glutamate Receptors – mGluRs'. Highlights: Most popular group selective orthosteric agonists and their binding to the VFT domain are described. A few subtype selective orthosteric agonists and their binding to the VFT domain are described. orthosteric antagonists and their binding to the VFT domain are described. Drug-likeness of orthosteric ligands is outlined. New types of VFT ligands are included.